Influence of Natural Ventilation on Thermal Comfort in Semi-open Building under Early Summer Climate in the Area of Tropical Island. (2015) - Lu, Shilei; Fang, Kun; Qi, Yunfang; Wei, Shasha
Abstract: In this paper, The research was based on the thermal comfort questionnaires of people and the thermal comfort parameters test of the environment in semi-open lobby of ten starred hotels in Sanya. Through analyzing the thermal comfort questionnaire, the highest acceptable thermal comfort temperature in summer was 30.6 °C in the semi-open space with natural ventilation. It is not scientific to just use thermal sensation to judge the thermal comfort of human body, so thermal satisfaction, thermal preference and thermal comfort all should be considered in the human body thermal comfort evaluation.